2021
DOI: 10.32539/bsm.v5i4.381
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of No Footwear Use and Soil Helminth Incidence among Elementary School Children in Musi Rawas, South Sumatera, Indonesia

Abstract: Background: Soil-transmitted helminth infection (STH) is a parasite infection that involves humans being infected with roundworms by route of soil contamination. One billion individuals are infected with worms, including 568 million school-age children. Helminthiasis in elementary school-aged children was not documented in Musi Rawas Regency. This study's goal was to identify if not wearing footwear increases the incidence of parasitic infection.Methods: The research was a cross-sectional survey, followed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The baseline prevalence of hookworm infection among schoolchildren was 27.2% (95% CI 23.0–31.7) by the composite reference method. This result is in line with the study conducted in South Sumatra, Indonesia (25.9%) [ 24 ] and North Gondar (26.2%) [ 11 ]. However, the current result is lower than the studies in Debre Elias and Sanja districts, Amhara Region (63.2%) [ 25 ], and rural communities in Bahir Dar, Amhara Region (46.9%) [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…The baseline prevalence of hookworm infection among schoolchildren was 27.2% (95% CI 23.0–31.7) by the composite reference method. This result is in line with the study conducted in South Sumatra, Indonesia (25.9%) [ 24 ] and North Gondar (26.2%) [ 11 ]. However, the current result is lower than the studies in Debre Elias and Sanja districts, Amhara Region (63.2%) [ 25 ], and rural communities in Bahir Dar, Amhara Region (46.9%) [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it can also spread through soil contaminated by the feces of an infected person or through fertilizer (29). The research located in Musi Rawas Regency, South Sumatra, Indonesia obtains the results that Hookworm parasites became the most infecting school children in five primary school children in Tuah Negeri District, where parents working as farmers had the highest prevalence of STH (30). In line with research on schoolchildren from Jawi Primary School located in northwest Ethiopia, Hookworm is a parasite that infects schoolchildren the most (13.8%, p = 0.042) (22).…”
Section: Helminth Infection Agentmentioning
confidence: 55%
“…The use of footwear, a hygiene behavioral component is connected with the frequency of helminth infection in the study done in Bamendjou Community, Upper Plateaux Division, Western Cameroon (p = 0.04) (40). Similar research in Tuah Negeri, one of the subdistricts from Musi Rawas Regency including the province of South Sumatra, Indonesia mentions the incidence of helminth infection was found in primary school children who use less footwear (p = 0,000) (30).…”
Section: Footwear Use and Play On The Groundmentioning
confidence: 63%
“…Consistently with a study by Anegagrie et al, (2021) found that environmental factors were associated with hookworm infections at individual and domestic levels (Anegagrie et al, 2021). In addition, shoe-wearing was reported to be at a low level (Silvia et al, 2021) noted that not wearing shoes when performing farming tasks or going outside can lead to infection (Rahmi et al, 2021 andSuntaravitun andDokmaikaw, 2018). Although these were in contrast with a study by Ruth et al, (2021) who found that the rate of infection with soil-borne parasites was higher in females than males (Ruth et al, 2021 andTegen andDamtie, 2021) found the males and females had no difference in infection rates (Tegen and Damtie, 2021), researcher resists the previous logic.…”
Section: Sub-gained Issue For Suggestion Synthesismentioning
confidence: 96%